Rural Settlement Network of Ukraine (the Spatial Analysis of Changes) - Rudenko, L. H.; Bochkovska, A. I. (Ukrainian Geographical Journal, 2024)
In recent decades, with the intensification of urbanisation processes in many countries, there have been numerous notable changes in the size of the rural population, as well as in the number and structure of rural settlements. The purpose of this study is to identify and assess spatial changes in the settlement of the rural population of Ukraine from 1959 to 2021 based on the results of cartographic analysis. The sources of the study are census data for the relevant years (1959, 1970, 1979, 1989, 2001) and subsequent statistical observations. Spatial changes in the regional size and density of the rural population, as well as its territorial dispersion, are traced. Between 1959 and 2001, when the last census was conducted in Ukraine, the number of rural settlements in Ukraine decreased by 13,600. For the first time, the publication highlights certain changes in the characteristics of the rural settlement network, which are new aspects in studying its development.